Education setting-based health promotion in New Zealand: evaluating the wellbeing and vitality in education (WAVE) programme. (7th November 2017) - Calder, Kristi; Begg, Annabel; Thompson, Lee; Williams, Daniel; Bidwell, Susan; Brosnahan, Neil
Abstract: Wellbeing and vitality in education (WAVE) is an education setting based health promotion initiative in South Canterbury, New Zealand. A mixed method approach was used for assessing change over time. Over ninety percent of education settings (94%) were participating in WAVE ( n  = 95). A total of 73 education settings completed the questionnaire at both baseline and follow-up. Evaluation of the WAVE programme shows that a robust partnership between health and education sectors can provide the basis for high levels of participation and significant changes in practice across all levels of education and a whole province. Evaluation results included that professional development for staff in some health related topics had improved. There was evidence of increasing partnerships between schools and community. Teachers had become role models for health messages and students had taken on leadership roles. Although the approach was based on health promoting schools literature, early engagement with education settings allowed the development of a local programme and branding. The overall outcome of WAVE has been a culture change in South Canterbury, where promoting the health of students, staff and families is becoming part of normal business for education settings. The results provide reason for optimism regarding the careful use of a health promoting schools framework, working in partnership with a range of stakeholders towards improving the health and subsequent life chances of young people.